The role of literature and social sciences in the development of students' skills in education - Maloku, Flamur; Kamberi, Ferdi (International Journal of Innovative Research and Scientific Studies, 2025)
Through this paperwork research, we aim to explore and analyze the role and impact of social sciences literature in the development of students' skills and abilities in the process of education. The literature offers our students a great opportunity to learn and develop their knowledge in education to a higher level. This research was designed to be a tool for assessing and evaluating students' perceptions, targeting the students of the Social Sciences Department at Gjakova University and the students of the Education Department at Gjilan University. Our sample consists of 150 students from both aforementioned universities. The questionnaire is divided into two parts: the first part includes demographic variables such as gender, ethnicity, and academic profile. Meanwhile, the second part delves deeper into students' perceptions and evaluations regarding literature and sociology in the development of their skills in general education. In terms of methodology, the study focuses on two primary research methods: a quantitative study involving surveyed students from social sciences and education, and a focus group with selected students from the two faculties. The overall findings reveal that literature and social sciences significantly contribute to the development of students' critical thinking, analytical abilities, and social discourse, enhancing their academic, psychological, social, and cultural development. By exploring this relationship, the study presents a novel approach to integrating these disciplines, marking one of the first of its kind in Kosovo. Thus, the study's implications suggest significant recommendations not only for students and academic institutions but also for other stakeholders. It advocates for the integration of literature and sociology as a vital part of university curricula in new academic programs, emphasizing the importance of raising awareness about utilizing these disciplines within general and higher education for students.